Iranian Urology Association Coronavirus Disease 2019 (COVID-19) Taskforce Pamphlet (IUA-CTP) Recommended Practice based on National Epidemiologic Analysis - Ghahestani, Seyed Mohammad; Bonakdar Hashemi, Milad; yousefzadeh Kandevani, Naser; Borumandnia, Nasrin; Dadpour, Mehdi; Sharifiaghdas, Farzaneh (Urology Journal, 2020)
Since the emergence of Covid19 epidemics different guidelines and protocols have been published by Urology associations. Most of these recommendations have focused on the aptitude of any disease or condition for postponement. With the evolution of the outbreak, it is clear that postponement of procedures is not the policy we can rely on exclusively. We must know where do we stand? Where are we going in our country? How useful our recommendations have been for urology practitioners? We try to draw a clearer although-to some extent- conjectural picture and to adjust our protocols to this picture of outbreak evolution. Assuming that anything in this predicament is subject to unexpected changes. For these goals, we raise these arguments in three sections. First, where do we stand and where are we going? Explaining the present situation and best available statistics of the disease, the velocity the disease is spreading and our approximate predicted date its subsidence or partial remission. In a web form survey, we tried to evaluate that in the absence of a clear picture of outbreak progress in a specific area, how useful experts’ points of view will be for the urologists working in non-referral centers especially in relevance to equivocal and challenging cases. Will there be any significant difference at all? In the third section, we try to give the plot to guide scheduling or postponing procedures in any given are according to the level of involvement. Here we considered both the characteristics of the special urology condition and also the situation and progress of the outbreak in that area